A comparison study of 589 and 650 nm on improving stored whole blood stability by irradiation with a low-power diode pumping solid-state laser - Safa Hassan Mohammed; Mustafa Salih Al Musawi; Bassam Talib Al-Gailani (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the effects of diode-pumped solid-state laser irradiation with 589nm and 650nm wavelengths on the stability of stored red blood cells in vitro. Method: This is an intervention study that was conducted from April to July 2021 at the Physiology and Medical Physics Laboratory, College of Medicine, Mustansiriyah University, Baghdad, Iraq, and comprised samples of healthy, adult human blood that were put in tubes with citrate-phosphate dextrose-adenine as an anticoagulant. The blood sample was divided into eight equal aliquots and stored for 21 days at 4ºC. The stability test was done on days 0, 7, 14 and 21 of storage time for non-irradiated and radiated aliquots. For 15 minutes, the irradiated aliquots were subjected to a diode-pumped solid-state laser with a wavelength of 589nm or a laser with a wavelength of 650nm at frequencies of 30, 50 and 70 J/cm². Data was analysed using SPSS 24. Results: Exposure of the whole blood to 589nm and a radiation dose of 70J/cm², 50J/cm² and 30J/cm² was associated with a significant reduction in the percentage of haemolysis that ranged 23-42% throughout the whole storage time. Exposure of the whole blood to 650nm wavelength low-level laser therapy and a radiation dose of 70J/cm², 50J/cm² and 30J/cm² was associated with much less reduction in the percentage of haemolysis that ranged 5-9% throughout the whole storage time. Conclusions: Both 589nm and to some extent 650nm low-level laser irradiation generally reduced haemolysis. The wavelength of 589nm lasers had a more effective influence than the 650nm counterpart in improving the stored red blood cells. Key Words: Lasers, Solid-State, Hemolysis, Light Therapy, Erythrocytes, Anticoagulants, Radiation, Phosphates, Citrates, Glucose, Adenine